2009
DOI: 10.2174/1874297100902010069
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology and Virulence Characteristics of Klebsiella pneumoniae Strains Isolated from Hospital-Associated Infections

Abstract: Abstract:Purpose: The present study aimed to confirm by classical and molecular laboratory methods hospitalassociated outbreaks due to virulent Klebsiella pneumoniae strains.Methods: Eighty three Klebsiella pneumoniae strains isolated from new-born patients, adults and hospital environment and devices in five hospital units, were analyzed for resistance to antibiotics, including last generation cephalosporins, sensitivity to bacteriophages and pulsed-field gel electrophoresis profiles in order to evaluate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
1
6
0
2
Order By: Relevance
“…The results from this investigation is similar to that of (Damian et al, 2009;Lim et al, 2009) who reported 33.34% and 23.5% ESBL producing strains from human clinical cases respectively. Similarly (Khanfar et al, 2009) reported 17% ESBL positive K. pneumoniae strains from nosocomial and community-acquired infections and all ESBL positive isolates were sensitive to imipenem while in contrast to present study resistant to gentamicin and ciprofloxacin.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results from this investigation is similar to that of (Damian et al, 2009;Lim et al, 2009) who reported 33.34% and 23.5% ESBL producing strains from human clinical cases respectively. Similarly (Khanfar et al, 2009) reported 17% ESBL positive K. pneumoniae strains from nosocomial and community-acquired infections and all ESBL positive isolates were sensitive to imipenem while in contrast to present study resistant to gentamicin and ciprofloxacin.…”
Section: Discussionsupporting
confidence: 90%
“…(Parasakthi et al, 2000) studied nosocomial outbreak of multidrug-resistant Klebsiella pneumoniae and reported that ESBL producing isolates were completely resistant to ceftazidime and sensitive to imipenem and ciprofloxacin, which is similar to the present study. In the present study, we were able to identify different resistotypes similar to that of (Damian et al, 2009) that of (Mansour et al, 2014) who studied the antibiotic resistance pattern of K. pneumoniae obtained from nasopharyngeal swab of respiratory tract infected camels and other domestic animals. They reported that K. pneumoniae isolates were resistant to β-lactams antibiotics like cefotaxime, ceftazidime, ceftriaxone and aztreonam with 100% resistance to amoxicillin and ampicillin.…”
Section: Discussionmentioning
confidence: 71%
“…Формирование «госпитальных штаммов» клебсиелл в основном ассоциируется с их способностью продуцировать β-лактамазы расширенного спектра и карбапенемазы [11]. Инфекции, вызванные этими штаммами бактерий, отличаются резистентностью возбудителя к большинству широко используемых в практике цефалоспоринов и, как следствие, значимой летальностью [13,14]. К причинам неэффективности антибиотикотерапии относят также способность клебсиелл к формированию биопленки на поверхности различных медицинских изделий, особенно на сосудистых и мочевых катетерах, эндотрахеальных трубках [15,16].…”
unclassified
“…Other infections caused by this organism include urinary tract infections, wound infections, abscesses, sepsis, infections of the blood stream, inflammation and diarrhea (Hackstein et al, 2013). K. pneumonia strains exhibit different virulence factors which give the bacteria the ability to invade the host, including the structures of capsular polysaccharides (CPS; the K antigen), lipopolysaccharide (LPS; the O antigen), secreted toxins, drug resistance and genetics , serum resistance, production of urea and enterotoxin, type 1 and type 3 adhesions, factors involved in aggregative adhesions and siderophores (Damian et al, 2009;Abbott, 2003;Eisenstein and Zaleznik, 2000;Chang et al, 2000;Podschun and Ullman, 1998;Cheng et al, 1991). Capsule plays a very important role in virulence (Sikarwar and Batra, 2011).…”
Section: Annals Of Tropical Medicine and Publicmentioning
confidence: 99%